Protective effects of Zingiber cassumunar Roxb. extract against UVB‐induced oxidative stress in Wistar albino rats (Rattus novergicus Berkenhout, 1769) - Dian Ayuning Tyas; Nastiti Wijayanti; Tri Rini Nuringtyas; Subagus Wahyuono (Indonesian Journal of Biotechnology, 2024)
Protecting the skin from the effects of UVB radiation using natural products is crucial in the cosmeceutical industry. This study aims to investigate the protective effects of Bangle (Zingiber cassumunar Roxb.) against UVB‐induced skin damage in Wistar albino rats. The rhizomes were macerated using 70% ethanol v/v, followed by n‐hexane to obtain n‐hexane soluble and n‐hexane insoluble fraction. The antioxidant properties of the ethanol extracts and n‐hexane soluble fraction were evaluated using a 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay. The study also examined the antiphotoaging properties through reactive oxygen species (ROS) scavenging assay, matrix metalloproteinase‐1 (MMP‐1) expression, and tyrosinase expression against UVB radiation in Wistar albino rats. The results demonstrated that the Z. cassumunar extract and fraction effectively converted DPPH radicals into a more stable compound. Analysis revealed the presence of Benzene, 4‐(1Z)‐1,3‐butadien‐1‐yl‐1,2‐dimethoxy‐ and (E)‐4‐(3,4‐Dimethoxyphenyl) but‐3‐en‐1‐ol as the primary compounds in both the extract and fraction, suggesting their contribution to the observed activity. Furthermore, Z. cassumunar compounds could reduce UVB‐induced ROS production and may protect against skin photoaging by changing the expression of MMP‐1 and tyrosinase levels in Wistar albino rats. These findings suggest that Z. cassumunar holds promise for preventing skin aging.